2x+4y=16
x-7=-4y
4y=16-2x
<span>4y=16-2(-4y+7)
4y=16+8y-14
-4y=2
-4y/-4=2/-4
<u>y=-0,5</u>
2x=16-4(-0,5)
2x=16+2
2x/2=18/2
<u>x=9
</u>
C</span>
Answer:
g(3) = 11
g(-3) = 16
g(-1) =3
Step-by-step explanation:
For g(3)
g(x)= x² +2
g(3) = 3² + 2
g(3) = 9+2
g(3) = 11
For g(-3)
g(x) = -3x + 7
g(-3) = -3(-3) + 7
g(-3) = 9 + 7
g(-3) = 16
For g(-1)
g(x) = x² + 2
g(-1) = (-1)² +2
g(-1) = 1+2
g(-1) =3
Step-by-step explanation:
factor 4 out of the variable terms, as this helps.
but my approach is simply to define the target and then calculate "backwards".
we want to find
(ax + b)² = a²x² + 2abx + b²
and now we compare with the original equation :
a²x² = 4x²
a² = 4
a = 2
2abx = 16x
2×2×bx = 16x
4b = 16
b = 4
b² = 16, but we have only 3, so we need to subtract 16-3 = 13 from the completed square.
so, our equation is
(2x + 4)² - 13 = 0
(2x + 4)² = 13
2x + 4 = sqrt(13)
2x = sqrt(13) - 4
x = sqrt(13)/2 - 2